Pengaruh kebugaran, IMT dan umur terhadap risiko diabetes melitus pada Pegawai Negeri Sipil - Cut Nasrulsyah; Fahmi Ichwansyah; Hermansyah Hermansyah; Asnawi Abdullah; Meutia Zahara (AcTion: Aceh Nutrition Journal, 2022)
The prevalence of non-communicable diseases (NCD) in Aceh Province is very high. It is a health problem and the main cause of death due to diabetes, hypertension, stroke, etc. The reason is the low level of community fitness due to lack of movement, low activity and wrong eating patterns. This study aims to measure the effect of fitness, BMI and age on the risk of diabetes mellitus in civil servants. The study used a cross-sectional design and was carried out at the Aceh Provincial Health Office in 2021. The sample was a civil servant from the Aceh Provincial Health Office. Ninety-seven people were taken randomly. The characteristic data collection was conducted by interview. It used BMI and anthropometric data obtained from weighing and measuring the height to determine nutritional status. Blood glucose was collected by laboratory examination of Hba1C using A1CNOW Plus 3021 to detect diabetes mellitus. Fitness data was obtained from jogging (1,6 km) using the Rockport method to obtain the VO2 Max value. Data analysis used the Linear Regression test at a significance level of 95%. The results showed that fitness (p=0,039) and BMI (p=0,011) affected the risk of diabetes (p<0,05), while the age factor was not associated with diabetes (p=0,365) in civil servants. The dominant factor that influences the risk of diabetes is BMI (OR= 4,1). In conclusion, fitness and BMI greatly influence the risk of diabetes in civil servants at the Aceh Provincial Health Office, while the age factor has no significant effect.